2014
DOI: 10.5941/myco.2014.42.2.93
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Chronicle of the GenusCordycepsFr., the Oldest Valid Genus in Cordycipitaceae (Hypocreales, Ascomycota)

Abstract: The earliest pre-Linnaean fungal genera are briefly discussed here with special emphasis on the nomenclatural connection with the genus Cordyceps Fr. Since its valid publication under the basidiomycetous genus Clavaria Vaill. ex L. (Clavaria militaris L. Sp. Pl. 2:1182, 1753), the genus Cordyceps has undergone nomenclatural changes in the post-Linnaean era, but has stood firmly for approximately 200 years. Synonyms of Cordyceps were collected from different literature sources and analyzed based on the species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…white to yellow). A thorough review of the taxonomic history of Cordyceps was provided by Shrestha et al . (2014b) , who concluded that Cordyceps is the oldest accepted generic name in this clade and is typified by a sexual morph.…”
Section: Taxonomymentioning
confidence: 99%
“…white to yellow). A thorough review of the taxonomic history of Cordyceps was provided by Shrestha et al . (2014b) , who concluded that Cordyceps is the oldest accepted generic name in this clade and is typified by a sexual morph.…”
Section: Taxonomymentioning
confidence: 99%
“…Externally, they produce clavate, cylindrical or thin filamentous, filiform stroma on the hosts. The history of exploring and identifying Cordyceps fungi is long and stretches back to the 17th century [8]. One of the most popular fungi is Ophiocordyceps sinensis (syn.…”
Section: Introductionmentioning
confidence: 99%
“…Cordyceps Fr. and allied species are very curious groups of fungi, with long botanical history starting in pre-Linnaean era (Shrestha et al 2014). Recent molecular phylogenetic studies showed that Cordyceps sensu lato is not monophyletic and is intercepted by plant pathogenic genera Claviceps Tul., Balansia Speg., Epichloë (Fr.)…”
Section: Phylogenetic Classification Of Cordycepsmentioning
confidence: 99%